Mechanisms For The Formation Of Methodological Skills In Working With Educational Information In Future Teachers Based On A Cognitive Approach - Begjanova Nuriya (Zien Journals, 2025)
This article discusses the specific features and directions of developing the methodological skills and professional competence of future teachers based on a cognitive approach, methods for developing the methodological skills of future teachers in processing and presenting information, innovative and traditional methods that require their application, and these methods
Keywords: cognitive approach; methodological skills; competence